2015
DOI: 10.1017/s0022029914000715
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterisation of a glutamic acid-containing peptide with calcium-binding capacity from whey protein hydrolysate

Abstract: The bioavailability of dietary ionised calcium is affected by intestinal basic environment. Calcium-binding peptides can form complexes with calcium to improve its absorption and bioavailability. The aim of this study was focused on isolation and characterisation of a calcium-binding peptide from whey protein hydrolysates. Whey protein was hydrolysed using Flavourzyme and Protamex with substrate to enzyme ratio of 25:1 (w/w) at 49 °C for 7 h. The calcium-binding peptide was isolated by DEAE anion-exchange chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…After the addition of calcium, changes of the -NH stretching vibration were observed, the red shift from 3410.21 to 3398.41 cm −1 in the amide-A band indicated that the -NH 2 and -NH groups participated in the chelating reaction and that the Ca−N bonds replaced the N−OH (hydrogen bonds). 39 The absorption band of SPH at 1654.36 cm −1 was an amide I band possessing -CO stretching vibrations. It appeared as two peaks (1654.62 and 1647.93 cm −1 ) when combined with calcium, indicating that the carboxylic group involved in the covalent binding reaction with the metal ions.…”
Section: Articlementioning
confidence: 99%
“…After the addition of calcium, changes of the -NH stretching vibration were observed, the red shift from 3410.21 to 3398.41 cm −1 in the amide-A band indicated that the -NH 2 and -NH groups participated in the chelating reaction and that the Ca−N bonds replaced the N−OH (hydrogen bonds). 39 The absorption band of SPH at 1654.36 cm −1 was an amide I band possessing -CO stretching vibrations. It appeared as two peaks (1654.62 and 1647.93 cm −1 ) when combined with calcium, indicating that the carboxylic group involved in the covalent binding reaction with the metal ions.…”
Section: Articlementioning
confidence: 99%
“…Considering nutritional quality and cost, many animal sources, aquatic sources and plant sources are suitable as protein sources to produce protein hydrolysates for calcium‐chelating peptides (Sun et al ., ). Calcium‐chelating peptides have been isolated and characterised from various sources, including cow milk casein (Meisel & Frister, ), whey (Huang et al ., ), tilapia fish muscle and scales (Charoenphun et al ., ; Chen et al ., ) and soy (Lv et al ., ) proteins. Many studies show that the calcium‐chelating activity of protein hydrolysates depends on enzymes types, degree of hydrolysis, amino acid composition, specific groups of amino acids and molecular weight (Liu et al ., ; Guo et al ., ; Sun et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, bioactive peptides are suitable candidates as supplements to improve calcium absorption in the gastrointestinal tract of the human body. Currently, calcium-chelating peptides have been isolated and characterized from various sources, including whey [9], alaska pollock backbone and skin [10], shrimp [11], chlorella [12], bovine serum [13], and wheat germ [14]. …”
Section: Introductionmentioning
confidence: 99%